2017
DOI: 10.1186/s12936-017-1897-6
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo susceptibility and genotyping of Plasmodium falciparum isolates from Pikine, Senegal

Abstract: BackgroundThe monitoring of Plasmodium falciparum sensitivity to anti-malarial drugs is a necessity for effective case management of malaria. This species is characterized by a strong resistance to anti-malarial drugs. In Senegal, the first cases of chloroquine resistance were reported in the Dakar region in 1988 with nearly 7% population prevalence, reaching 47% by 1990. It is in this context that sulfadoxine–pyrimethamine temporarily replaced chloroquine as first line treatment in 2003, pending the introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…One way of assessing the in vitro drug susceptibility of parasite species lacking representative culture-adapted lines is through using an ex vivo platform, where infected erythrocytes are removed from the patient and exposed to serial dilutions of drugs in a 96-well plate. These parasites are then allowed to grow for a period of time (up to one complete life cycle usually, as they do not re-invade if not culture-adapted) and the survivors can be quantified using either microscopy or measuring [ 3 H]hypoxanthine incorporation ( Chaorattanakawee et al, 2017 ; Fatih et al, 2013 ; Kaewpongsri et al, 2011 ; Mbaye et al, 2017 ; Rangel et al, 2018 ). Obtaining ex vivo non-falciparum parasites is a challenge, especially in a non-endemic setting such as the UK.…”
Section: Discussionmentioning
confidence: 99%
“…One way of assessing the in vitro drug susceptibility of parasite species lacking representative culture-adapted lines is through using an ex vivo platform, where infected erythrocytes are removed from the patient and exposed to serial dilutions of drugs in a 96-well plate. These parasites are then allowed to grow for a period of time (up to one complete life cycle usually, as they do not re-invade if not culture-adapted) and the survivors can be quantified using either microscopy or measuring [ 3 H]hypoxanthine incorporation ( Chaorattanakawee et al, 2017 ; Fatih et al, 2013 ; Kaewpongsri et al, 2011 ; Mbaye et al, 2017 ; Rangel et al, 2018 ). Obtaining ex vivo non-falciparum parasites is a challenge, especially in a non-endemic setting such as the UK.…”
Section: Discussionmentioning
confidence: 99%
“…However, with widespread discontinued use, numerous molecular-epidemiological studies showed that there was return of chloroquine susceptibility in P. falciparum field isolates [4]. This is supported by ex vivo [5][6][7][8][9][10][11][12][13][14][15][16] and in vivo drug-susceptibility studies [5,17,18]. Findings suggest that chloroquine might be reused in the future as an option for the treatment and/or chemoprophylaxis on the condition that chloroquine sensitivity is maintained in the area.…”
Section: Introductionmentioning
confidence: 99%
“…However, with widespread discontinued use, numerous molecular-epidemiological studies showed that there was return of chloroquine susceptibility in P. falciparum field isolates [4]. This is supported by ex vivo [5][6][7][8][9][10][11][12][13][14][15][16] and in vivo drug-susceptibility studies [5,17,18]. Findings suggest that chloroquine might be re-used in the future as an option for the treatment and/or chemoprophylaxis on the condition that chloroquine sensitivity is maintained in the area.…”
mentioning
confidence: 94%